Repurposing Metformin in Nondiabetic People With HIV: Influence on Weight and Gut Microbiota. (11th September 2020) - Isnard, Stéphane; Lin, John; Fombuena, Brandon; Ouyang, Jing; Varin, Thibault V; Richard, Corentin; Marette, André; Ramendra, Rayoun; Planas, Delphine; Raymond Marchand, Laurence; Messaoudene, Meriem; Van der Ley, Claude P; et al.
Abstract: Background: People with HIV (PWH) taking antiretroviral therapy (ART) may experience weight gain, dyslipidemia, increased risk of non-AIDS comorbidities, and long-term alteration of the gut microbiota. Both low CD4/CD8 ratio and chronic inflammation have been associated with changes in the gut microbiota of PWH. The antidiabetic drug metformin has been shown to improve gut microbiota composition while decreasing weight and inflammation in diabetes and polycystic ovary syndrome. Nevertheless, it remains unknown whether metformin may benefit PWH receiving ART, especially those with a low CD4/CD8 ratio. Methods: In the Lilac pilot trial, we recruited 23 nondiabetic PWH receiving ART for more than 2 years with a low CD4/CD8 ratio (<0.7). Blood and stool samples were collected during study visits at baseline, after a 12-week metformin treatment, and 12 weeks after discontinuation. Microbiota composition was analyzed by 16S rDNA gene sequencing, and markers of inflammation were assessed in plasma. Results: Metformin decreased weight in PWH, and weight loss was inversely correlated with plasma levels of the satiety factor GDF-15. Furthermore, metformin changed the gut microbiota composition by increasing the abundance of anti-inflammatory bacteria such as butyrate-producing species and the protective Akkermansia muciniphila. Conclusions: Our study provides the first evidence that a 12-week metformin treatment decreased weight and favored anti-inflammatory bacteria abundance in the microbiota of nondiabetic ART-treated PWH. Larger randomized placebo-controlled clinical trials with longer metformin treatment will be needed to further investigate the role of metformin in reducing inflammation and the risk of non-AIDS comorbidities in ART-treated PWH. Abstract : The ability to keep an HIV elite controller status is not permanent. We showed that, independently to protective MHC-I HLA alleles, elevated level of anti-CMV IgG is linked to CD4 T-cell decay in a Canadian cohort of elite controllers.